The stem cell session of the 7th Yazd International Congress and Student Award in Reproductive Medicine held at Shahid Sadoughi University of Medical Sciences - Zahra Borzouie; Somayyeh Sadat Tahajjodi; Behrouz Aflatoonian (Shahid Sadoughi University of Medical Sciences, 2017)
This paper summarizes the proceedings of the stem cell session of the “7th Yazd International Congress and Student Award in Reproductive Medicine” held at Shahid Sadoughi University of Medical Sciences, Yazd, Iran, on 28-30 April 2017. Here, we collected the papers of the session entitled: “Stem Cells, Good manufacturing practice, and tissue engineering”, that presented and discussed at this meeting by the international and national experts of the overlaps of the fields of stem cells and reproductive medicine, and the translation of these efforts towards practical application in regenerative medicine.